Design, Synthesis of Newer Substituted of 1,3,4-Oxadiazole Analogues and Study for Anticancer Activity (International Journal of Food and Nutritional Sciences, 2022)
oxadiazole; structure activity relationship, anticancer activity, cytotoxicity.